The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jvs.2020.10.067
|View full text |Cite|
|
Sign up to set email alerts
|

Endovascular interventions for claudication do not meet minimum standards for the Society for Vascular Surgery efficacy guidelines

Abstract: Objective: Because the treatment of intermittent claudication (IC) is elective, good short-and long-term outcomes are imperative. The objective of the present study was to examine the outcomes of endovascular management of IC reported in the Vascular Quality Initiative and compare them with the Society for Vascular Surgery guidelines for IC treatment to determine whether real-world results are within the guidelines.Methods: Patients undergoing peripheral vascular intervention for IC from 2004 to 2017 with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 47 publications
(47 reference statements)
0
12
0
Order By: Relevance
“… 7 Also, evidence is mounting that restenosis rates can be exacerbated by the misuse of atherectomy. 3 , 8 Because of concerns regarding restenosis and occlusion, which plague any endovascular intervention to the femoropopliteal segment, different strategies have been used, including covered stents, which theoretically only have a risk of restenosis and occlusion at the margins of the stent, because neointimal ingrowth cannot occur in the body of the stent graft itself. The use of covered stents has resulted in good success in limited series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Also, evidence is mounting that restenosis rates can be exacerbated by the misuse of atherectomy. 3 , 8 Because of concerns regarding restenosis and occlusion, which plague any endovascular intervention to the femoropopliteal segment, different strategies have been used, including covered stents, which theoretically only have a risk of restenosis and occlusion at the margins of the stent, because neointimal ingrowth cannot occur in the body of the stent graft itself. The use of covered stents has resulted in good success in limited series.…”
Section: Discussionmentioning
confidence: 99%
“… 2 The widespread use of endovascular techniques has been called into question regarding the efficacy and durability, with one study using patient-reported outcomes suggesting only a 32% sustained benefit at 2 years for endovascular intervention for PAD. 3 Multiple modalities are available of endovascular treatment of femoropopliteal atherosclerotic disease, none of which has demonstrated clear superiority over the others. Atherectomy, drug-coated balloon angioplasty, bare metal stents, and covered stents have all been proposed as effective methods to treat femoropopliteal lesions.…”
mentioning
confidence: 99%
“…Traditionally, the main strategy to prevent/manage atherosclerosis relies on controlling its risk factors, i.e., blood LDL levels, hypertension or life habits like smoking. Although, atherosclerotic occlusion can be removed by atherectomy, a common recurrence of the disease within 2 years after the surgical intervention in up to 50% of patients has been noted ( Bath et al, 2021 ). Interestingly, this fact may be similar to the well-known recurrence of malignant growth after the surgical removal of tumour mass.…”
Section: Inflammation Leads To Atheroma Formation and Tumour Cell Mas...mentioning
confidence: 99%
“…Pivotal clinical trials have found that some operations may be no more beneficial than sham surgery or non‐surgical alternatives, including lumbar fusion surgery and meniscectomy for degenerative disease, 4,5 arthroscopy for knee osteoarthritis, 6 and spinal cord stimulation for low back pain 7 . This problem is not limited to open surgery; some interventions in cardiac and peripheral vascular systems may not be beneficial for people with stable cardiovascular disease 8,9 …”
mentioning
confidence: 99%